2016
DOI: 10.1007/s10661-016-5339-7
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation of nutrients and metals in sediment, water, and phoomdi from Loktak Lake (Ramsar site), northeast India: phytoremediation options and risk assessment

Abstract: In order to determine the potential of phoomdi to accumulate nutrients and metals, 11 dominant species belonging to 10 different families, sediment, and water were analyzed for a period of 2 years from the largest freshwater wetland of north-east India, Loktak (Ramsar site). Results revealed nutrient (TN and TP) and metal (Fe, Mn, Zn, and Cu) compartmentalization in the order phoomdi > sediment > water. Iron concentrations in water (0.37 ± 0.697 to 0.57 ± 1.010 mg L(-1)) and sediments (81.8 ± 0.45 to 253.1 ± 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…The use of aquatic plants for heavy metal removal has been extensively reviewed [5] [6] [15]- [17] and widely studied both under laboratory [18]- [20] as well as field conditions [21]- [27]. Insights from all these studies point to the existence of a wide variation in the ability of different plants to accumulate heavy metals and the ability of a particular genera or species to accumulate different amounts of the same heavy metal from different sites.…”
Section: Introductionmentioning
confidence: 99%
“…The use of aquatic plants for heavy metal removal has been extensively reviewed [5] [6] [15]- [17] and widely studied both under laboratory [18]- [20] as well as field conditions [21]- [27]. Insights from all these studies point to the existence of a wide variation in the ability of different plants to accumulate heavy metals and the ability of a particular genera or species to accumulate different amounts of the same heavy metal from different sites.…”
Section: Introductionmentioning
confidence: 99%
“…Ideally, a good phytoextractor should have a TF > 1. It means that the plant is translocating the pollutant into the aerial part and hence is liberating the roots and rhizomes for more pollutant to be absorbed [1,[38][39][40]. However, Baker [41] proposed an additional category apart from the one mentioned above, that is an "Indicator" category, which is when uptake and transport of metals to the shoots are regulated so that internal concentration reflects external levels.…”
Section: Determination Of Bioaccumulation and Translocation Factormentioning
confidence: 99%
“…This is likely because on the shore of the Valsequillo reservoir, particularly close to the sampling point VAL03, there is a human settlement called San Baltazar Tetela, which discharges their residual waters into the reservoir. This wastewater can contain metals coming from a wide variety of domestic household products, such as toothpaste, cosmetics, batteries, and cleaning materials that contain trace concentrations of these metals [39] and thus enriching the content of these metals in that specific zone. In addition, Water hyacinth plants that cover the Valsequillo reservoir absorb metals from water during the growing period, but as proved by Jackson [53], during senescence, the plant is susceptible to release metals along with the Water hyacinth plants tissues into the surrounding water.…”
Section: Physicochemical Parameters and Potential Toxic Metal (Ptms) mentioning
confidence: 99%
“…Aquatic plants are suitable for detecting environmental changes [ 36 , 37 ]. Many studies have demonstrated the ability of macrophytes to phytoremediate heavy metals [ 20 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. Analysis of bottom sediments and biological samples helps to determine the overall content of PTEs and their impact on the aquatic environment [ 46 ].…”
Section: Introductionmentioning
confidence: 99%